Public Policy and Community Empowerment in the Development of Sheep and Goat Farming in Indonesia - Nilamcaya, Mus; Bastoni, Bastoni; Nurhawaeny, Endah; Widyani, Retno (ann4publisher@gmail.com, 2024)
The primary goal of public policy regarding the growth of sheep and goat farming in Indonesia is to make these commodities more competitive and valuable in fulfilling the demands of the animal protein industry and the needs of farmer welfare. To boost operational effectiveness and increase the process base's value for sheep and goat commodities, sheep and goat farmers affiliate with one another and establish businesses. An analysis of the literature was the study's methodology. The findings indicated that the expansion of goat and sheep farming had to focus on utilizing more locally available natural resources and reducing the use of chemicals. In order to do this, more sustainable and health-safe organic farms can be established. Government initiatives in public policy give the development of sheep and goat husbandry in Indonesia more strategic importance. With an integrated closed-loop system concept, the Indonesian Goat Sheep Breeders Association (HPDKI) aims to fast-track the strategic role of sheep and goat farming development, starting with sustainable breeding and progressing through fattening off. The strategic programs of HPDKI include cluster-based closed-loop livestock corporations, integration of value-added production systems, building farmer capacity, organizational and institutional strengthening, and culture-based livestock breeding systems. These programs are intended to stimulate development in the livestock and animal health subsector. The development of sheep and goat farming in Indonesia is primarily driven by official policy, which aims to boost productivity, add value, and the sector's strategic importance in satisfying animal protein demands and improving farmer welfare.